Pengaruh stres kerja dan ketidakamanan kerja terhadap turnover intention pada the lerina hotel nusa dua bali - Komang Aryati, Gusti Ayu; Ratna Sari, Ni Putu; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas; Vol 4 No 2 (2020): Vol.4,No.2,2020DO - 10.24843/JKH.2020.v04.i02.p01, 2020)
Abstra ct                     Based of the research by the increasing problem of turnover intention at The Lerina Hotel Nusa Dua, Bali. Variables that caused of increased turnover intention are variables of work stress and work insecurity. The purpose of this study is to determine the influence of job stress and job insecurity on turnover intention at The Lerina Hotel Nusa Dua Bali, and to determine the effect job stress and job insecurity on turnover intention. Techniques data collection by observation, interviews, questionnaires, documentation, and literature studies. While the sampling technique is saturated sample with a number of respondents of 50 people. This research using descriptive qualitative and quantitative technique consisting of a likert scale, validity test and reliability test, classic assumption test, correlation test, multiple linear regression analysis, t test, F test, and determination test.                   The results show s that Fcount (39,020)> Ftable (3.20) with a sig value of 0,000 or <? (0,05). This shows that job stress variables (X1) and job insecurity (X2) simultaneously have a positive and significant effect on turnover intention (Y) at The Lerina Hotel Nusa Dua. The t-test or partial results show that job stress has a total influence of 2,566 with a significance level of 0.014 <0.05 and job insecurity has an influence of 5,849 with a significance level of 0,000 <0.05 which means that job stress and job insecurity have a positive and significant effect on employee turnover intention in The Lerina Hotel Nusa Dua. Furthermore, the results of the determination test showed that the effect of job stress and job insecurity on turnover intention was 62.4% and the remaining 37.6% was influenced by other factors not included in this study.     Key Word : Job Stress, Job Insecurity, Turnover Intention, and The Lerina Hotel Nusa Dua Bali